Article Commentary: Environmental Sanitation Crisis: More than just a health issue - Peter A. Harvey (Environmental Health Insights, 2008)
The global environmental sanitation crisis cannot be denied: well over a century after the sanitary revolution in 19th century Europe, 40% of the world's population still lacks access to improved sanitation. Important lessons from the past must be applied today if the crisis is to be averted. Sanitation has suffered from a lack of prioritization for as long as it has remained the poor relation to water supply. The International Year of Sanitation 2008 provides an opportunity to separate the two and give sanitation the emphasis it requires. The economic argument for sanitation must be articulated and non-health incentives for improved sanitation exploited. Environmental sanitation results in a multitude of socio-economic benefits and can contribute positively to all the Millennium Development Goals. Community-led bottom-up approaches, rather than supply-led or technology-driven approaches, are most effective in increasing and sustaining access to sanitation but need to be implemented at scale. Targeted strategies for urban and school sanitation are also required. Evidence-based advocacy can help develop the political will that is now needed to ensure sufficient public sector investment, leadership, legislation and regulation to ensure that the fundamental human right of access to sanitation is realized.